A bottom-up proteomics workflow for a system containing multiple organisms - Bai, Hongxia; Collins, Leonard B.; André, Marcos Rogério [UNESP]; Breitschwerdt, Edward B.; Williams, Taufika Islam (Wiley, 2022)
Rationale: Discovery proteomics has been popularized to be essential in the investigator's biological toolbox. Many biological problems involve the interplay of multiple organisms. Herein, a bottom-up proteomics workflow was developed to study a system containing multiple organisms to promote a thorough understanding of how each interacts with the others. Methods: A label-free quantification proteomics workflow was developed with nanoscale liquid chromatography coupled to tandem mass spectrometry (nanoLC-MS/MS). This protocol describes a bottom-up proteomics workflow used to study differential protein expression in the context of fleas (Ctenocephalides felis felis) experimentally infected by the bacterium Bartonella henselae, the etiological agent of Cat Scratch Disease (CSD). Results: Step-by-step instructions are provided for protein extraction, protein cleanup, total protein measurement, nanoLC-MS/MS data acquisition, and data analysis using Proteome Discoverer software. Comprehensive and exhaustive details are included to promote the adoption of this proteomics workflow in other laboratories. Conclusion: A proteomics protocol is detailed for a system containing multiple proteomes from different taxonomic lineages using CSD (cats bitten by fleas infected with Bartonella henselae) as a model. The operating protocol can be readily applied to other label-free proteomics work involving multiple proteomes from taxonomically distinct organisms.